Human Resource Management in Government Bureaucracy: Strategies and Challenges in Recruitment, Training, and Employee Retention - Erni Murniarti; JFX Susanto Soekiman; Mashudi Mashudi; Putri Anditasari; Yoan Zelika (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2023)
Government bureaucracy plays a central role in providing effective and quality public services. The effectiveness and quality of good government bureaucracy are highly dependent on competent human resource management. This research aims to investigate strategies related to employee recruitment, training, and retention in the context of government bureaucracy. Using a descriptive qualitative approach, research data was obtained through secondary data analysis which included previous studies relevant to the research topic. The results of this research found the importance of integrating human resource strategies in maintaining the quality of employees in government organizations, as well as supporting positive transformation in work culture and better public services. In the context of human resource management, recruitment, training, and retention strategies must be aligned to achieve the long-term goals of government organizations, namely providing quality public services that are responsive to community needs.